Repeated interaction in standard setting. Issue 3 (5th October 2018) - Larouche, Pierre; Schuett, Florian
Abstract: Standardization may allow the owners of standard‐essential patents to charge higher royalties than would have been negotiated ex ante. In practice, however, standard‐setting efforts are often characterized by repeated interaction and complementarities among technologies. These features give firms that contribute technology to standards both the ability and the incentive to avoid excessive royalties by threatening to exclude other technology contributors from future rounds of standardization if they charge royalties exceeding 'fair, reasonable, and nondiscriminatory' (FRAND) levels. We show that such an outcome can be sustained as a subgame‐perfect equilibrium of a repeated standard‐setting game and examine how the decision‐making rules of standard‐setting organizations (SSOs) affect the sustainability of FRAND royalties. Our analysis provides a novel justification for super‐majority requirements and other rules frequently adopted by SSOs.